DEBRIS FLOW DISASTER MITIGATION THROUGH COMMUNITY-BASED INTEGRATED SEDIMENT MANAGEMENT (BEST PRACTICE IN MT. MERAPI AREA, INDONESIA) - Kazuhiko Otani; Suharyanto Suharyanto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
Mt. Merapi is one of many active volcanoes in Indonesia which erupts frequently. The small eruption occurred nearly every year, whereas the big ones occurred at approximately once every five years. The eruption often produces impacts at both positive and negative view points, such as production of sediment as construction material and damage on infrastructures due to debris flow occurrences respectively. The eruption produces two types of disasters, i.e. primary disaster (such as ash fall, pyroclastic flow, and lava flow), and secondary disaster such as debris flow. This paper presents the long term effort on the development of community participation in the sand mining management as one of strategic disaster mitigation activities. The raising awareness of the community on the necessity of conducting proper sand mining management and its effect on reducing the risk due to debris flow disaster has shown the effectives of the approach being introduced. The local government acceptance on the presence of the community participation in the whole system of sediment management may involve further collaboration between the local government authority and community society in the future.